Foreign Accent Syndrome As a Psychogenic Disorder: A Review - Keulen, Stefanie; Verhoeven, Jo; De Witte, Elke; De Page, Louis; Bastiaanse, Roelien; Mariën, Peter (Frontiers in Human Neuroscience, 2016)
In the majority of cases published between 1907 and 2014, FAS is due to a neurogenic etiology. Only a few reports about FAS with an assumed psychogenic origin have been published. The present article discusses the findings of a careful database search on psychogenic FAS. This review may be particularly relevant as it is the first to analyze the salient features of psychogenic FAS cases to date. This article hopes to pave the way for the view that psychogenic FAS is a cognate of neurogenic FAS. It is felt that this variant of FAS may have been underreported, as most of the psychogenic cases have been published after the turn of the century. This review may improve the diagnosis of the syndrome in clinical practice and highlights the importance of recognizing psychogenic FAS as an independent taxonomic entity.